2017
DOI: 10.1038/s41598-017-18368-w
|View full text |Cite
|
Sign up to set email alerts
|

Voruciclib, a clinical stage oral CDK9 inhibitor, represses MCL-1 and sensitizes high-risk Diffuse Large B-cell Lymphoma to BCL2 inhibition

Abstract: Aberrant regulation of BCL-2 family members enables evasion of apoptosis and tumor resistance to chemotherapy. BCL-2 and functionally redundant counterpart, MCL-1, are frequently over-expressed in high-risk diffuse large B-cell lymphoma (DLBCL). While clinical inhibition of BCL-2 has been achieved with the BH3 mimetic venetoclax, anti-tumor efficacy is limited by compensatory induction of MCL-1. Voruciclib, an orally bioavailable clinical stage CDK-selective inhibitor, potently blocks CDK9, the transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 47 publications
(62 reference statements)
2
61
1
Order By: Relevance
“…There are various studies that have successfully associated CDK9 inhibition with MCL-1 depletion and subsequent induction of tumor cell death (41). However, many come with study design caveats such as prolonged CDK9 inhibition (15,42), a narrow focus on one indication and/or a limited number of preclinical models (8,43), and use of nonselective compounds (14,44) that make it difficult to draw firm conclusions. This study overcame those limitations by utilizing the selective CDK9 inhibitor, AZD4573, and applying multiple approaches to interrogate the mechanism of action of CDK9 inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various studies that have successfully associated CDK9 inhibition with MCL-1 depletion and subsequent induction of tumor cell death (41). However, many come with study design caveats such as prolonged CDK9 inhibition (15,42), a narrow focus on one indication and/or a limited number of preclinical models (8,43), and use of nonselective compounds (14,44) that make it difficult to draw firm conclusions. This study overcame those limitations by utilizing the selective CDK9 inhibitor, AZD4573, and applying multiple approaches to interrogate the mechanism of action of CDK9 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Despite clinical development of multiple inhibitors with CDK9 activity, the precise mode of action driving antitumor effects has yet to be fully elucidated, although their preclinical activity has been attributed predominantly to depletion of MCL-1 protein and subsequent induction of tumor cell death (13)(14)(15). MCL-1 is an antiapoptotic, BCL-2 family protein whose high expression has been associated with increased cancer cell survival that translates to chemotherapy resistance and poor patient prognosis (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…The consequence of this promiscuity has been elegantly demonstrated in T98G glioblastoma cells, where introduction of a kinase-dead, dominant-negative mutant CDK9 results in a gene expression profile that is distinct from that induced by flavopiridol [26]. While the latter study emphasizes the polypharmacology of flavopiridol, identifying precise targets associated with clinical toxicity has been challenging [27]. In addition, the pharmacokinetic properties of flavopiridol and other inhibitors such as dinaciclib require intravenous dosing, with different infusion schedules being explored in specific trials [4,5,7,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Although they appeared to share a similar mechanism of action in vitro, CDKI-73 has an advantage of better pharmacokinetics and higher oral bioavailability than flavopiridol. Moreover, the dose-limiting toxicity due to lack of selectivity and prolonged CDK9 inhibition narrowed the therapeutic index of flavopiridol (Dey et al, 2017;Lanasa et al, 2015), whereas CDKI-73 has shown a remarkably reduction of toxicity in non-cancerous cells . Western blot analysis of the tumours collected from xenografted mice treated with CDKI-73 confirmed its inhibition of CDK9 in vivo (Fig.…”
Section: Discussionmentioning
confidence: 99%